Memory in children with symptomatic temporal lobe epilepsy - Catarina A. Guimarães; Patrícia Rzezak; Daniel Fuentes; Renata C. Franzon; Maria Augusta Montenegro; Fernando Cendes; Kette D. Valente; Marilisa M. Guerreiro (Arquivos de Neuro-Psiquiatria)
In children with temporal lobe epilepsy (TLE), memory deficit is not so well understood as it is in adults. The aim of this study was to identify and describe memory deficits in children with symptomatic TLE, and to verify the influence of epilepsy variables on memory. We evaluated 25 children with TLE diagnosed on clinical, EEG and MRI findings. Twenty-five normal children were compared with the patients. All children underwent a neuropsychological assessment to estimate intellectual level, attention, visual perception, handedness, and memory processes (verbal and visual: short-term memory, learning, and delayed recall). The results allowed us to conclude: besides memory deficits, other neuropsychological disturbances may be found in children with TLE such as attention, even in the absence of overall cognitive deficit; the earlier onset of epilepsy, the worse verbal stimuli storage; mesial lesions correlate with impairment in memory storage stage while neocortical temporal lesions correlate with retrieval deficits.